Determinandts of Investment decision on Lecture college in Bekasi - Hidayat, Wastam Wahyu (International Journal of Business and Applied Economics, 2024)
This The aim of the research is to determine the effect of financial literacy and income on investment decisions for staff and lecturers at the Technical College in Bekasi. The sample of this study was 70 respondents who were staff and lecturers of the Technical College in Bekasi. The results of the research data were collected through questionnaires which were processed and analyzed using regression analysis, classical assumption test, quality test used was test and reliability test using Cronbach alpha. The results showed that financial literacy and income partially have a positive and significant effect on investment decisions, because the Sig of each variable is smaller than 0.05, namely; Sig,0.000 and Sig.0.003. Simultaneously, it shows that there is an effect of financial literacy and income on investment decisions for the Staff and Lecturers of the Technical College in Bekasi because Signya: Sig. 0.000.